Spontaneous bilateral external jugular venous aneurysm: A series of two case reports - Srishti Singh, MBBS, DNB; Neha Singh, MBBS, MD; Shivam Singh, MBBS (Radiology Case Reports)
Venous aneurysms are fairly rare entities as compared to arterial aneurysms. Very few cases of spontaneous external jugular venous aneurysms are documented in literature without any previous history of trauma. Bilateral involvement is a further scarce finding. We present a case series of two such patients, who presented with unilateral, and painless neck swelling, exaggerated on Valsalva. Ultrasound in both cases showed cystic swelling with luminal continuity with EJV. CT of the neck with contrast confirmed the findings. Further the contralateral External jugular veins in both the patients showed similar smaller outpouchings. Both the patients gave no past history of trauma. Therefore, considering the clinical details and imaging findings, the diagnosis was made as spontaneous EJV aneurysms. Since both the patients had no signs of expansion of the aneurysms or any complication, they were safely discharged with close follow up. The importance of this series revolves around the rare entities which can easily be missed or misdiagnosed. Vascular pseudoaneuryms are encountered frequently in presence of trauma. However, venous aneurysms are rare entity. Many a times, they can mimic venous malformation and lymphangioma clinically. But with proper clinical details and extensive evaluation of imaging findings they can be easily diagnosed and should not missed as management varies significantly between an aneurysm, pseudoaneurysm and malformation. The clinicians must be vigilant for any concerning signs or complications in the aneurysms as if it is enlarging, then the patient should be referred to a vascular surgeon for further management.